2012
DOI: 10.1063/1.4768790
|View full text |Cite
|
Sign up to set email alerts
|

Small polaron migration associated multiple dielectric responses of multiferroic DyMnO3 polycrystal in low temperature region

Abstract: Utilizing temperature dependent dielectric/impedance spectroscopy, multi-dielectric responses involving two dielectric relaxations (DRs) and two magnetic-order-associated dielectric anomalies were observed in polycrystalline DyMnO3. It is elucidated that both DRs’ dynamics, established in terms of equivalent circuit model and small polaron (SP) theories, are closely linked with localized SP migration features. Namely, low-temperature relaxation process can be attributed to short range polaronic variable-range-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…This means that the complex impedance contains only one constituent contribution at the atomic level, which can be considered as the source of the colossal dielectric permittivity, while it has nothing to do with any grain boundary effect. 25 The results are also in accordance with amorphous phase TiO 2 without apparent grain boundaries and long-range order as discussed earlier.…”
Section: Resultssupporting
confidence: 88%
“…This means that the complex impedance contains only one constituent contribution at the atomic level, which can be considered as the source of the colossal dielectric permittivity, while it has nothing to do with any grain boundary effect. 25 The results are also in accordance with amorphous phase TiO 2 without apparent grain boundaries and long-range order as discussed earlier.…”
Section: Resultssupporting
confidence: 88%
“…It is considered that the activation energy will be lower in the spin ordered state where electron hopping between ordered spins spend lower energy as compared to the hopping energy in the paramagnetic regime. [36,37] This is suggestive of a correlation between the magnetic and dielectric properties in YNMO.…”
Section: Dielectric and Impedance Measurementsmentioning
confidence: 76%
“…where N(E F ) is the density of localized states at the Fermi level, and ξ is the decay length of the localized wavefunction. This approach has been used in the interpretation of conductivity data of several oxides [37][38][39], including DyMnO 3 [22]. The temperature dependence of the dc conductivity of both samples, obtained by equation ( 1), was analysed with equations ( 3) and (4).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning microstructural and dielectric inhomogeneity, the dielectric response of polycrystalline ceramics is a rather more challenging open issue. Although there are few dielectric investigations of TbMnO 3 [21], DyMnO 3 [22], and DyMn 1−x Fe x O 3 [23] polycrystals, with the exception of the recent work by Yang et al [22], the reported dielectric data were mainly concentrated in the fairly high temperature range above 100 K. Considering the rich physical phenomena at low temperatures, extending dielectric studies to lower temperatures is of fundamental interest. Systematic investigations could help elucidate the correlations between dielectric properties, electrical transport and magnetic ordering, and provide new insights into the nature of magnetoelectric and magnetocapacitive effects in rare-earth manganites.…”
Section: Introductionmentioning
confidence: 99%